IMPROVING THE FINANCIAL PERFORMANCE OF MSMES IN UMBULHARJO, YOGYAKARTA THROUGH FINANCIAL LITERACY, FINANCIAL INCLUSION, AND ENTREPRENEURIAL ORIENTATION - Susana Ema Kelen; Risal Rinofa; Pristin Prima Sari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze how the financial performance of MSMEs in Umbulharjo District, Yogyakarta can be improved through financial literacy, financial inclusion, and entrepreneurial orientation. This study uses a quantitative approach with data collection through questionnaires distributed to 130 MSMEs in the Umbulharjo area. The data obtained were analyzed using the Smartpls application version 4. The results of the study indicate that financial literacy has a significant influence on the financial performance of MSMEs, while financial inclusion does not have a significant effect. Meanwhile, entrepreneurial orientation is proven to have a positive and significant influence on the financial performance of MSMEs in Umbulharjo.